Fatores associados ao comprometimento emocional e osteomuscular em cuidadores formais e informais de idosos - Figueiredo, Leandro Corrêa (Universidade Federal de São Carlos, 2019)
Introduction: The caregiver burden is most explored in emotional aspects. However, there is still little information about the risk factors and physical symptoms in the caregivers. Objective: Describe and analyze the of physical and emotional burden factors and symptoms among formal and informal caregivers of the elderly. Methods: Cross-sectional and descriptive study, carried in the urban region of São Carlos city. 123 informal caregivers and 39 formal caregivers, in addition to 125 elderly residents in the community and 140 institutionalized elderly participated. Socio-demographic questionnaires and personal and work-related characteristics were applied to caregivers and the elderly. Questionnaires on physical and emotional burden symptoms were applied to caregivers and a scale assessing the risk for movement and transfer was applied in the elderly and the environment where they were. Results: The physical symptoms in the caregivers were more frequent than the emotional. Both groups of caregivers have a high number of working hours per day (between 6 - 12 h/day). Informal caregivers are older, have fewer days off, no guidance or training about how to take care of the older adults, and carry out more extra activities besides care (p<0.05). Formal caregivers reported a higher perceived exertion related to handling/transfer activity. The regressions demonstrated that the worst functional capacity of the elderly and that the increase in the perception exertion of the caregiver are the main factors related to musculoskeletal symptoms (p <0.05).
Factors associated with emotional and musculoskeletal impairment in formal and informal elderly caregivers
Keywords: Cuidador; Idoso; Dor musculoesquelética; Saúde do trabalhador; Caregivers; Aged; Musculoskeletal pain; Occupational health; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL